RESOLVING CONTRACTOR COMMITMENT CHALLENGES IN PROJECT DELIVERY BY USING CONCETPUAL SYSTEM DYNAMICS MODELS - Olatunji Ayodeji AIYETAN; Dillip DAS (Journal of Construction Project Management and Innovation)
Contractors play a vital role in construction projects. However, their lack of commitment is argued to be one of the major barriers against successful project delivery. This investigation was aimed at to explore how contractor commitment challenges can be resolved to improve their performance in the project delivery. A survey research method was used to collect data, and Likert scale was applied to evaluate the relative importance of the contractor commitment challenges. Followed by conceptual System Dynamics (SD) modelling principle was used to develop causal feedback relationships among the variables influencing contractor commitment and to develop mechanisms to resolve the challenges. Findings suggest that lack of experience, skill, inadequate supervision, and lack of control over the subcontractors lead to contractor’s inefficiency. Poor planning and scheduling, poor professional management, poor execution of projects, ineffective/outdated equipment, and inefficiency of labour force result in poor quality of work and delay. In addition, design and documentation challenges disrupt the contractors’ schedule. The interlinkage among these variables hinders contractor commitment. However, policy/strategic interventions based on the causal feedback relationships among contractor efficiency, and (1) capacity building; (2) professional management; (3) construction methods; and (4) involvement of the contractor and client in the design process would enable the contractors to overcome their challenges to meet their commitment and improve efficiency in project delivery.